Seed and seedling variation of Pterocarpus angolensis DC from selected natural populations of Malawi - Munthali, Chimuleke Rowland Yagontha (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.